Interleukin-1 beta augments release of norepinephrine, dopamine, and serotonin in the rat anterior hypothalamus - Shintani, F (J Neurosci, 1993)
We investigated the effects of interleukin-1 beta (IL-1 beta), administered directly into the rat anterior hypothalamus (AHY), on monoamine release in the same region by using a brain microdialysis technique and an HPLC-electrochemical detection system. First, to study the local effects of IL-1 beta, we used a microdialysis probe equipped with a microinjection tube for administering IL-1 beta in the same region into which the probe had been inserted. IL-1 beta (1 ng) injected directly into the AHY elicited release of norepinephrine (NE), dopamine (DA), and 5-HT, as well as increases in their metabolites, 4- hydroxy-3-methoxyphenylglycol, 3,4-dihydroxyphenylacetic acid, 4- hydroxy-3-methoxyphenylacetic acid, and 5-hydroxyindole-3-acetic acid, in the AHY. Vehicle alone exerted no effect on monoamine release. Although the elevated levels of NE and DA persisted for more than 6 hr after injection of IL-1 beta, the elevated levels of 5-HT were transient. Second, in order to investigate whether this effect of IL-1 beta is a direct action in the AHY, we performed in vitro experiments using hypothalamus slices. IL-1 beta (0.1 and 1 nM) increased the levels of each monoamine released from hypothalamic slices in a dose- dependent manner. These findings suggest that IL-1 beta acts directly on the hypothalamus to induce release of NE, DA, and 5-HT. Third, the roles of prostaglandins (PGs) in NE release in the AHY elicited by direct injection of IL-1 beta were examined.(ABSTRACT TRUNCATED AT 250 WORDS)